Improvement of time forecasting models using a novel hybridization of bootstrap and double bootstrap artificial neural networks - Nurul Hila Zainuddin (Tanjong Malim, 2019)
Improvement of time forecasting models using a novel hybridization of bootstrap and double bootstrap artificial neural networks by Nurul Hila Zainuddin